Systematic review of built environment attributes of walkability: cases of Malaysia - Demdoum, Khair Eddine; Mohd Yunos, Yazid; Ujang, Norsidah; Utaberta, Nangkula (Chulalongkorn University - Faculty of Architecture, 2024)
Walkability has gained considerable traction in recent years as a key concept for promoting sustainable urban environments and healthier lifestyles. Built environment attributes such as infrastructure, streetscape design, land use mix, and street connectivity were found to have a high impact on walking behavior. However, due to the context-specific nature of walkability, where attributes deemed important in one context may not hold the same significance in another, this study aims to examine walkability attributes and methods within the Malaysian context. The goal is to offer valuable insights for researchers and policymakers operating in similar contexts. This study employed a systematic review following the PRISMA guidelines. A comprehensive search of SCOPUS and Google Scholar identified and assessed studies related to walkability in Malaysia. Rigorous screening and application of inclusion criteria yielded 32 Malaysian articles published between 2011 and 2021 for detailed review. Data extraction focused on specified factors including data source, built environment attributes, unit of analysis, and type of walking. The results identified both similarities and differences in the influence of built environment attributes on walking behavior in Malaysia compared to global patterns. Micro-scale factors, such as the aesthetics and attractiveness of walkways (65%), and safety and security (59%), were found to be leading factors in creating walking-friendly environments. Conversely, macro-level attributes, including density (15%) and mixed land use (18%), did not show a significant impact. This reliance on perceived assessments may struggle to capture the complexity of actual density and diversity, leading to inconsistent results. However, data collection and analysis approaches require further refinement. Future Malaysian research may prioritize the use of GIS-based walkability indexes to comprehensively measure walkability and improve the validity and accuracy of assessments. Additionally, consideration should be given to the regional transferability of these indexes.